النظام المتكامل للمعلومات المحاسبية والإدارية وأهميته في الوحدات الاقتصادية (Journal of Accounting and Financial Studies ( JAFS ), 2006)
The organization is affected by and affects the attending environment. Whereas the accounting information system is one of the informational systems existing in any organization.     The research partake capability of developing information system in economic units through design “A Integrated System of Accounting and Management Information “to enable using the relationships of an integrated from all subsystems in economic unit specially: Accounting Information System (AIS) and Management Information System (MIS).     Also the research partake a set of basic requisites that will contribute in application An Integrated System of Accounting and Management Information such as: information system of management accounting, central database, technological devices, qualifying personal in: accounting, management and computer spheres.